2008
DOI: 10.1002/anie.200705018
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (+)‐Exiguolide

Abstract: Exiguolide (1) is a unique 16-membered macrolide isolated from the marine sponge Geodia exigua Thiele (order Astrophorida, family Geodiidae).[1] It specifically inhibits fertilization of sea urchin (Hemicentrotus pulcherrimus) gametes but not embryogenesis of the fertilized egg. The macrolide structure incorporates two cis-2,6-disubstituted oxane rings, one of which carries an exocyclic enoate appendage reminiscent of bryostatins. The unique structural features and interesting biological activity of 1 has gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…77,78 The oxidation of a complex substrate bearing a primary alcohol has been described by Hirama and co-workers (Scheme 5). ROMPM, 114,115,118,183 ROBn, 80,90,104,106,110,124,191,192 ROTr, 180 ROMe, 94,101,107,113,192 RONPhth, 88 RON=CMe 2 , 88 ArOAllyl, 193 ArOMe, 108,130,131,192,194,195 ArOBn, 127,131 ArOTBS, 174 R 2 NBoc, 174,[194][195][196][197] 208 This IBX analogue generates only water during the oxidation, while DMP releases acetic acid. When DMP was applied the required keto ester was obtained in only 60%, with 40% of the starting lactone recovered (Scheme 6).…”
Section: 76mentioning
confidence: 99%
“…77,78 The oxidation of a complex substrate bearing a primary alcohol has been described by Hirama and co-workers (Scheme 5). ROMPM, 114,115,118,183 ROBn, 80,90,104,106,110,124,191,192 ROTr, 180 ROMe, 94,101,107,113,192 RONPhth, 88 RON=CMe 2 , 88 ArOAllyl, 193 ArOMe, 108,130,131,192,194,195 ArOBn, 127,131 ArOTBS, 174 R 2 NBoc, 174,[194][195][196][197] 208 This IBX analogue generates only water during the oxidation, while DMP releases acetic acid. When DMP was applied the required keto ester was obtained in only 60%, with 40% of the starting lactone recovered (Scheme 6).…”
Section: 76mentioning
confidence: 99%
“…The significant biological properties and structural challenges have made the exiguolides attractive targetsf or synthesis. The first synthesis of (+ +)-exiguolide, an enantiomer of 1,h as been achieved by Lee et al, [7] and itsa bsolute configuration was also elucidated.T he total synthesis of the naturally occurring (À)-exiguolide (1)w as accomplished by Fuwa and Sasaki, [8] followed by Roulland, [9] Scheidt, [5] and Song. [10] The formal synthesis of 1 was also reported by Reddy et al [11] Furthermore, Fuwa investigated the structure-activity relation-ships of 1,i ndicating that the terminus of the side chain tolerates structural modificationa nd the C15 methyl group is not important but the C18m ethyl group is indispensable for the potent antiproliferative activity.H erein we report an ovel total synthesis of (À)-exiguolide (1)a nd 15-epi-exiguolide by utilizing two catalytic asymmetric reactions in entirely stereocontrolled manner.…”
Section: Introductionmentioning
confidence: 99%
“…1,3-Dioxanes, for example, can be synthesized with an excess of suitable aldehyde in presence of an acid catalyst. 12 It has been well established that either strong Lewis (e.g., TiCl 4 , TiBr 4 , InCl 3 , SnCl 4 , BF 3 .OEt 2 ) [13][14][15][16][17][18] or Brønsted acids (e.g., H 2 SO 4 , trifluoroacetic acid, p-toluenesulfonic acid, triflic acid) [19][20][21][22] have to be employed to the effective synthesis of these heterocycles. Some studies have demonstrated that concomitant usage of both types of acid catalysts has positive synergistic effect.…”
Section: Introductionmentioning
confidence: 99%